2015
DOI: 10.3855/jidc.6586
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic melioidosis presented as encephalomyelitis and subdural collection in two male labourers in India

Abstract: Two distinct and potentially deceitful cases of neurologic melioidosis are reported. Case 1: A 39-year-old alcoholic and uncontrolled diabetic male presented with cough, fever, and left focal seizures with secondary generalization. An magnetic resonance imaging (MRI) brain scan revealed a small peripherally enhancing subdural collection along the interhemispheric fissure suggestive of minimal subdural empyema. Blood culture grew Burkholderia pseudomallei. Patient was diagnosed with disseminated bacteraemic mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Melioidosis involving the central nervous system (CNS) is rare (seen in about 5%) [11], and can present in many ways including brain and epidural abscesses, encephalomyelitis (predominantly involving the brainstem), aseptic meningitis, dural venous sinus thrombosis and transverse myelitis [4, 12–17]. Isolated subdural collections associated with melioidosis, as seen in our patient, are rarely reported [12–14, 18–20]. A study from Darwin, Australia reported 14 cases with neurological involvement among 540 patients with melioidosis (10 with meningo-encephalitis, 2 with myelitis and 2 with cerebral abscesses); there were no cases of subdural collections [11].…”
Section: Discussionmentioning
confidence: 98%
“…Melioidosis involving the central nervous system (CNS) is rare (seen in about 5%) [11], and can present in many ways including brain and epidural abscesses, encephalomyelitis (predominantly involving the brainstem), aseptic meningitis, dural venous sinus thrombosis and transverse myelitis [4, 12–17]. Isolated subdural collections associated with melioidosis, as seen in our patient, are rarely reported [12–14, 18–20]. A study from Darwin, Australia reported 14 cases with neurological involvement among 540 patients with melioidosis (10 with meningo-encephalitis, 2 with myelitis and 2 with cerebral abscesses); there were no cases of subdural collections [11].…”
Section: Discussionmentioning
confidence: 98%
“…This commissural fiber spread may hence explain bilateral but asymmetric distributions of melioidosis lesions, favoring the hemisphere of initial infection. Supra and infratentorial structures as well as the spinal cord are involved in this dissemination, which results in difficulties in organism eradication and consequent poor clinical outcomes [18], [29].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough review of the literature yielded 31 well-detailed case reports of parafalcine SDEs [Table 1]. [1-3,5,6,8-11,13-17,19,23-27,29,31,35] Treatment strategies and outcomes of these cases and our own are discussed.…”
Section: Introductionmentioning
confidence: 99%